Effect of Machine Processing on the Quality of Animal Fat Reduced Rista : doi: 10.5958/2581-6616.2021.00001.3 - AI, Qureshi; SR, Ahmad; SA, Wani; AH, Sofi; MA, Rather; S, Nadeem; S, Shanaz; S Z, Hussain; B, Nazir; T, Nazir (Journal of Meat Science, 2022)
The traditional method of processing of high fat Rista (a mutton based emulsion type meat ball) being labour intensive process with little control on hygiene, demands an alternative method to mechanize the process. An experiment was thus designed with five treatments, including one traditionally prepared Rista Tc (with 20% animal fat) and four machines made products, viz. M0, M1, M2 and M3 (animal fat reduced from 0 to 75%). The results revealed that the parameters (measured on per cent basis) like emulsion stability (mean equal to 91.23 and 90.06 in Tc and M2, respectively), cooking yield (mean equal to 90.96 and 90.40 in Tc and M2, respectively), moisture (mean equal to 63.54 and 61.88 in Tc and M2, respectively), protein (mean equal to 15.77 and 15.98 in Tc and M2, respectively), fat (mean equal to 16.84 and 17.95 in Tc and M2, respectively) and ash content (mean equal to 2.36 and 2.02 in Tc and M2, respectively) of Rista made with machine method were comparable to that of the Rista made with traditional method. The values for various sensory parameters showed an increasing trend with the highest value in M2. The results of the instrumental colour values in terms of lightness (L*), redness (a*) and yellowness (b*) indicated that L*, a* and b* values were significantly (p≤0.05) affected by the replacement of animal fat with vegetable oil. Since the product remained acceptable up to M2 treatment, it was concluded that 50% of animal fat can be replaced with vegetable fat without affecting the quality of Rista, prepared by machine processing instead of traditional one.